Teacher Education Systems in Africa in the Digital Era - Oni, Adesoji; Adegoke, Bade (Book collections on Project MUSE., 2015)
Teacher education is vital for the realization of a nation's development aspirations. The conception, incubation and delivery of any national development policy, as well as the reform and implementation of extant policies, are driven by the quality of teachers and their products within a functional educational system. Indeed, national and global models of development, including the millennium development goals revolve round the frames of quality education, beginning with teacher education. It is therefore important to have functional teacher education systems in Africa to help its citizens explore the networking of the world as a global village. This is achievable through a systematic mobilization of national resources and visible commitment to the development of a modernized cadre of scientific and technological manpower. This book, Teacher Education Systems in Africa in the Digital Era is a rich exposition of theories and praxes essential for the development of teacher education in Africa. The book has immense benefits for teachers, teacher trainers, funding agencies, other stakeholders and policy makers.